Pediatric Cutaneous Larva Migrans: A Case Report from an Uncommon Region - Alghasham, Yazeed A (Scripta Medica, 2025)
Cutaneous larva migrans (CLM) is a skin infection caused by the of hookworm larvae, most commonly Ancylostoma braziliense or Ancylostoma caninum, within the outer layer of the skin. While CLM is primarily found in tropical and subtropical areas, occasional cases have been documented in other regions globally. This case report describes an 8-year-old boy from Saudi Arabia who presented with an unusual case of CLM which is not usually seen in our region of the world, characterised by a serpiginous, erythematous lesion on the medial aspect of his left little finger. The patient had no recent travel history, which made this case particularly noteworthy given the rarity of CLM in this region. The diagnosis was supported by clinical examination and imaging studies, which revealed inflammatory changes consistent with CLM. This case underscores the importance of recognising CLM, even in non-endemic regions and highlights the need for awareness among clinicians regarding the presentation and management of this parasitic infection.